Analisis Persepsional Siswa Sekolah Dasar pada Konten Video Animasi Dakwah Nabi Ibrahim - Pambayun, Ellys Lestari; Nugraha, M Irsyad Agung; Han, Muhamad Ibtissam (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2021)
This study aims to explore the perceptions of students of SD Karawaci Baru VIII Tangerang on the animated video The story of the Prophet Ibrahim (as) starting from the growing concern about animated video content and games that contain dangerous content or can damage the future of the nation's generation. This animated video produced by Al-Imran contains da'wah bil wisdom, da'wah bil mau'izah, and da'wah jidal bil ahsan in it. Therefore, the researchers tried to raise it through the theory of perception and the da'wah bil wasilah approach through the case study method with field observations and semi-structured interviews. The results of this study explain that the students of SD Karawaci Baru VIII Tangerang are supported by their parents and teachers in watching the animated video The Story of the Prophet Ibrahim as finding the meaning of wisdom, mau'izah hasanah, and jidal ahsan to be used as a means to build an umbrella or reaction filter against various information from outside that is not good or negative. Functionally (personal) and structurally (external environment) these students tend to like the story of the prophet Ibrahim, apart from their inner motives, as well as various needs that they don't get anywhere else or in their family. In addition, there is a desire to convey a call about the goodness, wisdom, and piety of Prophet Ibrahim which is suitable for learning these elementary school children. With order, creed, shari'ah, morals, and culture; animated videos become a small window to watch the various histories and stories of the noble prophets.